The Role of Risk in Achieving Sustainable Performance for Small and Medium Enterprises -A Case Study of a Sample of Algerian Enterprises- (Journal of Economic Additions, 2025)
This study examines risk-taking in Algerian SMEs and its impact on sustainable performance across economic, social, and environmental dimensions. Using 129 questionnaires from SME managers and directors, statistical analysis was conducted. Results show a significant effect of risk on overall sustainable performance and on each dimension at the 0.05 level. Among them, environmental performance was the most strongly influenced. The findings highlight the role of risk in fostering sustainable growth within SMEs. The study recommends measures to enhance sustainable performance across all three dimensions.Jel Classification Codes: D81، Q01، L25، M14، Q56.
Keywords: Keywords : Risk, Sustainable performance, Economic performance, Social performance, Environmental performance, SMEs.